2022
DOI: 10.1155/2022/8080197
|View full text |Cite|
|
Sign up to set email alerts
|

Research on the Teaching Method of Environmental Landscape Design Practice Based on IoT Network and Digital VR Technology

Abstract: The traditional practical teaching methods are based on teachers’ narration and demonstration, with few practical opportunities for students, lack of interactivity in teaching, low interest of students in teaching, and poor teaching effect. In order to improve the teaching effect of environmental landscape design and enhance students’ learning enthusiasm, a practical teaching method of environmental landscape design based on IoT network and digital VR technology will be studied. After guiding students to carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…In the article titled "Research on the Teaching Method of Environmental Landscape Design Practice Based on IoT Network and Digital VR Technology" [1], there was a spelling error in the second author's name in the author list, where "Liu Huadon" should have read "Liu Huadong." Tis is corrected in the article and is shown above.…”
mentioning
confidence: 99%
“…In the article titled "Research on the Teaching Method of Environmental Landscape Design Practice Based on IoT Network and Digital VR Technology" [1], there was a spelling error in the second author's name in the author list, where "Liu Huadon" should have read "Liu Huadong." Tis is corrected in the article and is shown above.…”
mentioning
confidence: 99%
“…Security and Communication Networks has retracted the article titled "Research on the Teaching Method of Environmental Landscape Design Practice Based on IoT Network and Digital VR Technology" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%